Governor General's House, Trinidad and Tobago, West Indies - (:unkn) unknown (Syncreators Ltd., Trinidad, 2009)
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Visitors to the Botanical Gardens enjoy the beautiful tropical flora with the residence of the Governor General, which is also situated on the ground of the gardens, in the background. This residence is known today as "The President's House".
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Architecture--Trinidad and Tobago; Trees--Trinidad and Tobago; President's House, The; Queen's Park Savannah